The goals and tasks of education - Robiyaxon Axmadjon qizi Anvarjonova; Superviser: M.M.Mirzakarimova (Science and Education, 2025)
This article examines the goals and tasks of education, its role in shaping an individual’s personality, and its impact on society. Furthermore, the modern principles of education, its significance in the pedagogical process, and its influence on societal progress are discussed.